Mexico and the Trans-Pacific Partnership Agreement (TPP). Issue 5 (19th October 2016) - Arredondo Hidalgo, Maria Guadalupe
ABSTRACT: This investigation analyzes the information in relation to Mexico and its commercial interaction within the Trans-Pacific Partnership Agreement (TPP). The principal purpose is to compare and analyze the commercial relations between Mexico and all members that correspond with the TPP, identifying the product opportunities that are commercialized within this trade bloc. This study is a descriptive investigation with a longitudinal correlational design. The comparative charts contain data that are directly related to economic information such as the history of the bilateral relations, strategic sectors, balance of trade, and the relevant products that are commercialized for each country involved.